Variability in social reasoning: the influence of attachment security on the attribution of goals - Dunfield, Kristen A.; Johnson, Susan C. (Frontiers in Psychology, 2015)
Over the last half decade there has been a growing move to apply the methods and theory of cognitive development to questions regarding infants’ social understanding. Though this combination has afforded exciting opportunities to better understand our species’ unique social cognitive abilities, the resulting findings do not always lead to the same conclusions. For example, a growing body of research has found support for both universal similarity and individual differences in infants’ social reasoning about others’ responses to incomplete goals. The present research examines this apparent contradiction by assessing the influence of attachment security on the ability of university undergraduates to represent instrumental needs versus social-emotional distress. When the two varieties of goals were clearly differentiated, we observed a universally similar pattern of results (Expt. 1a/b). However, when the goals were combined, and both instrumental need and social-emotional distress were presented together, individual differences emerged (Expt. 2, 3). Taken together, these results demonstrate that by integrating the two perspectives of shared universals and individual differences, important points of contact can be revealed supporting a deeper, more nuanced understanding of the nature of human social reasoning.